Analysis of Potential Bankruptcy with The Springate Method in Oil and Gas Subsector Companies Listed on The IDX 2018-2021 - Rahma, Hipta; Nurdiana, Diah (PT. Riset Press International, 2023)
Changes in world oil prices are a things that must be considered, because they can affect the selling price of crude oil and the profits to be obtained. Apart from that, the rupiah exchange rate against the US dollar is also one thing that needs attention. These conditions become one of the considerations for investors whether the results of the investment can provide profits or have a loss. One of the problems that must be considered is financial distress. The aims of this research is to use the Springate method to analyze the potential for bankruptcy in oil and gas subsector companies. This research uses a quantitative descriptive approach and data collection uses documentation techniques by taking secondary data from the website of the Indonesia Stock Exchange. The sample was selected using certain sampling criteria, so that the sample in this study amounted to 10 companies. The results of the analysis of potential bankruptcy using the springate method in 2018 to 2020 show that there are 8 companies in the distress zone and 2 companies in the safe zone. In 2021 there are 9 companies in the distress zone and 1 company in the safe zone.